Network a study of Felda Courier Service with a view developing an operation manual: special references to Felda Transport Corporation / Azham Kamarudin - Kamarudin, Azham (1988)
Felda is an organisation which consists of many corporations and main administration offices which have a daily contact with their branches within the nation. These resulted in the setting of NETWORK, a Felda Courier Service at the end of 1986,